Neck-MRI experience for investigation of survived strangulation victims - Christine Bruguier; Pia Genet; Jean-Baptiste Zerlauth; Fabrice Dédouit; Jochen Grimm; Reto Meuli; Tony Fracasso; Silke Grabherr (Forensic Sciences Research, 2020)
For the medicolegal evaluation of victims of survived strangulation, a neck-magnetic resonance imaging (MRI) can be performed for assessing lesions in the inner soft tissues (fat, muscles or lymph nodes, for example). In our institute, such MRI examinations have been performed for a test period of 4 years with the aim of evaluating the use of this tool by forensic pathologists and identifying medicolegal indicators for the performance of neck-MRI in surviving victims of strangulation. We retrospectively reviewed medicolegal reports from all victims examined during the test period. We extracted objective lesions (e.g. petechiae, bruising and abrasions) and reported clinical symptoms (e.g. vision disorder, dysphasia) from the reports. These findings were compared to those reported from the neck-MRI. In total, 112 victims were clinically examined after suspected strangulation. Eleven of these victims underwent an MRI examination of the neck. Eighty-four of the victims presented objective lesions during the clinical examination, with eight showing signs of both petechiae and bruising. Neck-MRI was performed in four of these eight victims and three of them showed lesions visible in MRI. Of 76 victims with bruising as the only objective finding, 66 victims described clinical symptoms. Of those 66 victims, seven were examined by MRI and two demonstrated lesions in MRI. When MRI was performed, relevant findings were detected in 45% of the cases. This leads to the suspicion that many more findings could have been detected in the other victims, if an MRI had been performed in those cases. Our results lead us to the conclusion that an MRI examination of victims of suspected strangulation is useful, and strict indications for its application should be established.